The impact of human resources policies and practices on organizational citizenship behaviors - Tinti, Joel Adame (2017)
This study aims to investigate how policies and practices in human resources (PPHR) impact organizational citizenship behaviors (OCB). The OCBs represent additional contributions from employees to their organizations and, somehow, individual actions expected in crisis scenario or changing time by managers. The theoretical basis contains Milkovich and Boudreau (1994), Dessler (2002), Demo et al. (2012), among others, to address PPHR and Handy (1978), Organ (1990) and Siqueira (2003) to OCB. We collect data from 156 employees of public, private and mixed companies located in the State of São Paulo. The results revealed significant impact from PPHR over OCB, and we evidence that only professional involvement exhibited significant relation. We also conclude that PPHR influence the dissemination of organizational image and creative suggestions from OCB factors. The results indicate suggestions where managers can act to extract, effectively, organizational citizenship behaviors from their employees.